EKSPLORASI FAKTOR PEMBENTUK WORK ENGAGEMENT GENERASI MILLENIAL di BANK BRI SURABAYA - Ikhwan Kholid (Trunojoyo University of Madura, 2022)
Bank BRI is one of the state-owned banks that has a large number of active millennial employees. This is done by bank BRI to answer future challenges and also to prepare young talents who will later occupy strategic positions in the company. The involvement of the millennial generation at Bank BRI is one of the strategies carried out by Bank BRI to attract potential customers from the millennial generation who in the next few years will replace consumers from the previous generation who have entered retirement or are no longer active in the business world due to age. and so forth. Besides the advantages of the millennial generation (Gen Y) for potential companies, there are also challenges for companies that are attached to the millennial generation, namely high turnover rates due to low work engagement from the millennial generation. This research is intended to add to the written literature and data and reveal things that can increase the Work Engagement of millennial generation employees in the banking sector, namely Bank BRI Surabaya, this research obtains results or findings of 6 things that are the forming factors of Millennial Generation Work Engagement at Bank BRI Surabaya, which include: 1. Salary 2. Health insurance (health insurance) 3. Career path 4. Work-Life Balance (work hours and leave) 5. Comfortable working atmosphere (room and attitude between employees) and 6. Appreciation from the leadership/company (performance allowances and praise.